Crystallization and preliminary X-ray diffraction analysis of suramin, a highly charged polysulfonated napthylurea, complexed with a myotoxic PLA2 from Bothrops asper venom - Murakami, Mário T. (2004)
Suramin is a highly charged polysulfonated napthylurea that interferes in a number of physiologically relevant processes such as myotoxicity, blood coagulation and several kinds of cancers. This synthetic compound was complexed with a myotoxic Lys49 PLA2 from Bothrops asper venom and crystallized by the hanging-drop vapor diffusion method at 18 °C. The crystals belong to the orthorhombic space group P212121, with unit cell parameters a=49.05, b=63.84 and c=85.67 Å. Diffraction data was collected to 1.78 Å.